ChatGPT in Moroccan Education Sector: Examining the Attitude of Student Acceptance and Usage Intent (Global Journal of Human-Social Science, 2025)
Abstract not found
Keywords: ChatGPT; perceived usefulness; perceived credibility; behavioral intention; educational technology; AI adoption; moroccan education sector